IoT based Solar Panel Cleaning Rover - Madhavan, Sruthi S; G., Arunjunai Raja; D., Harish Ragaventhira; G., Swathi (Journal of Electrical Engineering and Automation, 2024)
The primary objective of this proposed study is to design a system for effectively maintaining the cleanliness of solar panels, thereby enhancing their performance and longevity through an Internet of Things-based solar panel cleaning rover equipped with a sensors, and manual automation capabilities. A suite of sensors, including dust sensors, enables the rover to gather relevant data about the cleanliness status and ambient conditions surrounding the solar panels. Manual automation features empower users to intervene and control the rover’s movements and cleaning actions as needed, providing flexibility and customization in operation. Furthermore, the rover is designed to connect directly with water tanks, facilitating an autonomous water supply for the cleaning process. A sponge brush mechanism is integrated into the rover’s design to effectively remove dust from the solar panel surfaces. The proposed work has developed a prototype of the IoT-based solar panel cleaning rover, which has been tested to demonstrate its effectiveness in improving solar panel efficiency and reducing maintenance efforts.